Performance Evaluation of Freight Train Wooden Sleepers on the BH 77 Tegineneng Bridge - Pamursari, Nurmagita; Arifin Bustam, Hadyan; Nadya Karunia, Meutia; Agneshia Putri, Ananda (UKaRsT, 2024)
Rail transport is very important in supporting human mobility and distribution of goods for heavy loads such as coal. The BH 77 Tegineneng Bridge in Sumatra is a critical infrastructure that supports coal transportation. In its structural components, wooden sleepers are used on this bridge. The wooden sleepers used must withstand dynamic, shock, lateral, and longitudinal loads. This is to ensure the stability and operational safety of the bridge. This study aims to evaluate the performance of wooden sleepers on the BH 77 Tegineneng Bridge. A case study approach was used with field data on axle loads, including static and dynamic loads, collected and analyzed to determine the load distribution and structural response. The results show that the dynamic load with a Dynamic Amplification Factor of 1.86, coupled with a shock load reaching 56,784 kN, exerts significant stress on the sleepers. The wooden sleepers effectively absorb dynamic forces, distribute the load evenly, and demonstrate resilience under repeated loading cycles, with a maximum bearing load of 189.28 kN. These findings emphasize the suitability of wood as a sleeper material due to its elasticity and damping properties, which offers a durable and efficient railway infrastructure. This study contributes to demonstrating the characteristics of wooden sleepers as a basis for material selection in freight railway systems.